Influential factors of migration in Huancavelican women to a district of the Sierra Central of Peru - Segura Ilizarbe, Susy (2020)
The research was carried out with the objective of analyzing the factors that influence the migration of Huancavelican women. The study considered the procedures of the scientific method, as well as the deductive one; It is a basic research, with a quantitative approach and a non-experimental transactional design. The sample was made up of 168 Huancavelican mothers belonging to the Vaso de Leche Program of the Sapallanga district, to whom a questionnaire was applied, whose data were processed with the statistical program SPSS v24, and the Gauss Z hypotheses were tested for a proportion in large samples (n> 50), at 95% statistical confidence. It concludes by announcing that the Huancavelican migrants object of the study left their place of origin due to social factors (search for better employment opportunities, education for their children and better housing conditions), economic (low salary levels instead). of origin, and they go in search of better economic income to the city) and political (fear of persecution, political revenge and risk of losing their lives).